Pengaruh Pengetahuan Kewirausahaan, Self Efficacy dan Dukungan Sosial terhadap Minat Berwirausaha pada Mahasiswa di Kabupaten Jember - M. Mahfud Rizqy; Akhmad Suharto; Achmad Hasan Hafidzi (Universitas Nusantara PGRI Kediri, 2025)
This study aims to evaluate and analyze the influence of entrepreneurial knowledge, self-efficacy, and social support on entrepreneurial interest in students domiciled in Jember Regency. The approach used is quantitative descriptive with saturated sampling technique, involving 400 student respondents. To analyze the relationship between variables, this study uses multiple linear regression method to determine how much influence each independent variable has on the dependent variable. The results of the analysis show that all independent variables have a significant influence on entrepreneurial interest. Entrepreneurial knowledge has a significance value of 0.001 and a t count of 8.574, which is greater than the t table of 1.966. Self-efficacy also shows a significance of 0.001 with a t count of 10.208> t table. Likewise, social support has a significance value of 0.001 and a t count of 4.247> t table. These findings indicate that the three independent variables have a significant positive influence on increasing students' interest in entrepreneurship. This research is expected to provide important contributions in the development of entrepreneurship policies, especially in the academic environment of Jember Regency.